PENGARUH ELEMEN PEMASARAN MEDIA SOSIAL TERHADAP BRAND AWARENESS PADA INSTAGRAM HMP PRODI PENDIDIKAN MATEMATIKA UNIVERSITAS PGRI YOGYAKARTA: PENGARUH ELEMEN PEMASARAN MEDIA SOSIAL TERHADAP BRAND AWARENESS PADA INSTAGRAM HMP PRODI PENDIDIKAN MATEMATIKA UNIVERSITAS PGRI YOGYAKARTA - Didi Setiadi; anindita imam basri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study aims to determine the Effect of Social Media Marketing Elements on Brand Awareness on Instagram HMP Mathematics Education Study Program, Pgri Yogyakarta University. The research was conducted in the Special Region of Yogyakarta in 2022. The population of this study were all active students of the Mathematics Education Study Program, Universitas PGRI Yogyakarta. Sampling was done by non-probability sampling technique and using purposive sampling method taken from 120 respondents. This study uses multiple linear regression analysis. The results of the data regression analysis showed the following regression equation: Y = 1.903 + 0.260x1 + 0.131x2 + 0.217x3 + 0.182x4 + 0.110x5. The results of this study prove that Entertainment has a positive and significant effect on Brand Awareness, Interaction has a positive and significant effect on Brand Awareness, Trendiness has a positive and significant effect on Brand Awareness, Customization has a positive and significant impact on Brand Awareness, and E-WOM has a positive and significant effect on Brand Awareness. Brand Awareness. The results of the study of five independent variables have a simultaneous influence on Brand Awareness. This research is explained by adjusted R Square of 86.4%